Detection of Crime Using the Application of Regression Mechanism - Pathania, Minakshi; Awasthi, Isha (International Journal of Computer Sciences and Engineering, 2019)
Crime, an unlawful act, causes terror and threat to our society and is a major concern for national security. However, very negligible work has been done to develop models and methods to hold an active collaboration between forensic science and criminal investigation systems. The need is felt to develop a system that collects as well as categorise the data on crimes along with an analysis of crime affected areas identification. In this study, an efficient crime investigation system is proposed in which fuzzy rules and Regression clustering algorithm is employed to identify and detect crime affected region along with showing it on the map. The study of DATA GATHERING is incorporated for crime detection and prevention with an aim to provide a safer society to live.